2011
DOI: 10.1007/s00464-011-1791-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training and instrument type on performance in single-incision laparoscopy: Results of a randomized comparison using a surgical simulator

Abstract: LAP technique results in superior task performance with a shorter learning curve compared with SIL technique during a standardized training period. SIL-specific simulator training is better than LAP training alone to improve SIL performance. Neither S-ART nor D-ART instruments for SIL are associated with improved performance or shorter learning curve compared with STR instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 14 publications
4
21
0
Order By: Relevance
“…After completing three tasks of increasing difficulty, most of the CLS students (87%) were able to perform laparoscopic knot-tying, whereas this was accomplished by only 23% and 7% of the students, respectively, in the SPLS groups. This finding is consistent with the results of a previous study in which learning curves of novices appeared to be significantly longer for SILS techniques than for CLS procedures irrespective of the instruments used (straight, static-articulating, or dynamic-articulating) [6].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…After completing three tasks of increasing difficulty, most of the CLS students (87%) were able to perform laparoscopic knot-tying, whereas this was accomplished by only 23% and 7% of the students, respectively, in the SPLS groups. This finding is consistent with the results of a previous study in which learning curves of novices appeared to be significantly longer for SILS techniques than for CLS procedures irrespective of the instruments used (straight, static-articulating, or dynamic-articulating) [6].…”
Section: Discussionsupporting
confidence: 93%
“…Another group found conflicting data showing task scores of CLS compared with several single-port systems that did not differ significantly [7]. This might be attributed on the one hand to a relatively simple task (peg transfer) that had to be performed but on the other hand to the deployment of an internal camera rather than an operator-driven camera, which does not emulate the inherent instrument-camera clashing that occurs with clinical SILS (as stated by [6]). However, this is the first study to demonstrate the significant structural differences (i.e., the inherent enhanced difficulties in performance) of SPLS versus CLS in a large group of novice subjects.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The fellows involved in the study did have prior experience in advanced multiport laparoscopic procedures, but their median operating time was similar to the time required by residents. These difficulties of conventional laparoscopic proficient surgeons to translate these skills to SILS have also been reported by three laboratory-based studies comparing laparoscopic-and SILS-trained candidates [16][17][18]. Pucher et al concluded that the skills required for SILS are not automatically acquired through multiport laparoscopic experience [19].…”
Section: Discussionmentioning
confidence: 93%
“…The idea of SIL was irst proposed as a manual procedure, and grew into a daily surgical routine for general surgery in particular, especially for transoral, transanal, and transvaginal interventions [68][69][70]. The majority of manual SIL procedures were carried out using a single instrument for intervention, as laparoscopic SIL was found with compromised practicality, where the surgeon had to either reverse the motion of the instrument tips or cross his/her own hands to accommodate the immobilizing incision point, being a very counterintuitive exhaustive motoring task to add to the mental burden for the surgeon [71]. However, various studies have pointed out that, after proper training, the eicacy for laparoscopic SIL is at least as good as standard laparoscopy [72][73][74].…”
Section: Innovations For Accessibility: Sil and Notesmentioning
confidence: 99%